2013
DOI: 10.1093/scan/nst090
|View full text |Cite
|
Sign up to set email alerts
|

The voice of conscience: neural bases of interpersonal guilt and compensation

Abstract: People feel bad for inflicting harms upon others; this emotional state is termed interpersonal guilt. In this study, the participant played multiple rounds of a dot-estimation task with anonymous partners while undergoing fMRI. The partner would receive pain stimulation if the partner or the participant or both responded incorrectly; the participant was then given the option to intervene and bear a proportion of pain for the partner. The level of pain voluntarily taken and the activations in anterior middle ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(131 citation statements)
references
References 54 publications
7
121
1
2
Order By: Relevance
“…The right AI has been consistently associated with the processing of negative experiences in social interactions, such as broken promises (Baumgartner et al, 2009), social exclusion (Eisenberger, 2012, aggression (Krämer et al, 2007), interpersonal guilt (Yu et al, 2014), and being treated unfairly (Sanfey et al, 2003). More recently, Liljeholm et al (2014) demonstrated that the right AI tracked the interaction between intentionality and harmful consequence in an interpersonal transgression context, such that intentionally inflicted bodily harm (e.g., delivering aversive salty tea to the participants) elicited higher AI responses than unintentionally inflicted harm.…”
Section: Discussionmentioning
confidence: 99%
“…The right AI has been consistently associated with the processing of negative experiences in social interactions, such as broken promises (Baumgartner et al, 2009), social exclusion (Eisenberger, 2012, aggression (Krämer et al, 2007), interpersonal guilt (Yu et al, 2014), and being treated unfairly (Sanfey et al, 2003). More recently, Liljeholm et al (2014) demonstrated that the right AI tracked the interaction between intentionality and harmful consequence in an interpersonal transgression context, such that intentionally inflicted bodily harm (e.g., delivering aversive salty tea to the participants) elicited higher AI responses than unintentionally inflicted harm.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, left AI and dlPFC showed interactions between action agency and empathic pain, indicating that these regions may integrate the processing of self-generated errors with the social consequences of actions (Koban et al, 2013a). This integration process should be crucial for the generation of moral emotions such as guilt and shame that are associated with self-generated actions that have socially negative consequences (Chang et al, 2011;Koban et al, 2013a;Wagner et al, 2012b;Wagner et al, 2011;Yu et al, 2013).…”
Section: Social Influences On the Monitoring Of Self-generated Actionsmentioning
confidence: 99%
“…Functional neuroimaging studies have focused on imagining the event in which they felt the most guilt that they had ever experienced (Shin et al, 2000), intentionally or accidentally (Berthoz et al, 2006), gender difference (Michl et al, 2014), interpersonal (altruistic) guilt (Yu et al, 2014) or deontological guilt (Basile et al, 2011), compensation that might be stimulated by guilt (Yu et al, 2014), differences between guilty and embarrassment (Takahashi et al, 2004), compassion (Zahn et al, 2009a), pride (Zahn et al, 2009b), shame (Wagner et al, 2011) (Michl et al, 2014), and sadness (Wagner et al, 2011). In these functional studies, feelings of guilt were related to activation of the superior temporal/ inferior parietal lobule (IPL) including the superior temporal sulcus (STS) (Takahashi et al, 2004;Michl et al, 2014), ventromedial prefrontal cortex (vmPFC) (Zahn et al, 2009b;Morey et al, 2012), insula (Shin et al, 2000;Yu et al, 2014;Michl et al, 2014), amygdala, and subgenual cingulate cortex (SCC) (Zahn et al, 2009a(Zahn et al, ,b, 2013. A structural neuroimaging study dealing with healthy subjects linked proneness to guilt with individual variations in anterior brain regions (Zahn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%